(untitled) (Research, Society and Development, 2021)
This study aimed to evaluate the influence of the use of the microscope on the bond strength of fiberglass posts to dentin in the different root thirds. The crowns of sixty canines were sectioned with a diamond disc, and the roots were instrumented and filled (ProDesign Logic System 30.05 + obturation with AH Plus). Desobturation was performed with a drill corresponding to the pin diameter (DC 2, WhitePost). The roots were divided into six groups (n = 10): ACsm: Allcem and without a microscope; ACcm: Allcem and microscope; ACCsm: Allcem CORE without a microscope; ACCcm: Allcem CORE with microscope; RUsm: RelyX U200 without a microscope; RUcm: RelyX U200 with a microscope. The roots were cross-sectioned into slices of the cervical, middle and apical thirds and subjected to the bond strength test (Kratos- 0.5 mm / min / 100 Kgf). A stereomicroscope (40 x) was used to analyze the failure patterns of the samples. There was no statistically significant difference in the cervical thirds regardless of the cement used (p> 0.05). The apical third showed higher adhesion values in the group using a microscope and the self-adhesive cement (p <0.05). Conventional cement showed similar values in all root thirds (p> 0.05) and lower values compared to self-adhesive cement in the apical third (p <0.05). There was a predominance of the mixed failure pattern in the different groups and thirds. It can be concluded that the clinical microscope, the type of resin cement and the evaluated root third influenced the bond strength of fiberglass pins with the root dentin.